Multiantibiotic-resistant Pattern against Pathogenic Bacteria Isolated from Ready to Eat Food in Ludhiana - Kumar, Naresh (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The study was conducted to investigate the bacteriological contamination in the most common street food sold in Ludhiana at different places. 90 samples of street food samples were randomly collected from the selected part of Ludhiana. Samples investigated for the occurrence of bacteria by culturing them on selective and differential culture media. Methods: To detect the presence of pathogenic bacteria in food recommended method used like Spread Plate Techniques and identification of bacteria accomplished with the help of differential media and specific media, biochemical testing and molecular characterization also performed to ensure the particular strain of enteropathogenic bacteria. Results: The presence of pathogenic bacteria isolated from all street food were quite high, the percentage of Proteus sp. was 2%. Predominantly staphylococcus sp were found in street food. This was followed by Salmonella (6%) and Staphylococcus aureus (14%). Klebsiella sp. (5%) and Enterococcus sp. (2%) were least predominant in these foods. Conclusions: The study exhibited contagion may be due to poor techniques of food preparation adopted by the street food sellers and its big concern community well-being as well as bad for economy state and India, and there is the loss of 5.2% of national gross domestic product. These bacteria are also known for foodborne illnesses and toxic syndrome.